The Italian Scientific Society of Mafia and anti-mafia studies: genesis, nature, aims and perspectives (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The purpose of the contribution is to describe the Italian learned Society on Mafia and Anti-Mafia Studies, established in 2023. It is an interdisciplinary society composed of university researchers engaged in teaching, research and third mission. The role of universities and researchers, the constitutive process, its positioning in the academy, its organization, and its aims and activities are analyzed in the paper.
Keywords: Sisma; mafias; anti-mafia; learned society; mafia studies